Concept of the self - "Elliott, Anthony" (Cambridge, 2001)
This new and updated edition of "Concepts of the Self" remains the most lively, lucid and compelling introduction to contemporary controversies over the self and self-identity in the social sciences. Written by an author of international reputation, the book concentrates mainly on the work of social theorists and cultural analysts who have attempted to place the self in relation to psychological processes, social contexts and historical perspectives. Mead, Freud, Goffman, Foucault, Chodorow, Kristeva and Baudrillard are among the figures covered; the new edition also introduces material on iek. Elliott also connects debates about the self directly to identity politics, the sociology of personal relationships and intimacy, and the politics of sexuality. The book focuses upon cultural and political issues, and breaks new ground in integrating interdisciplinary perspectives. In analysing debates about the self, Elliott draws extensively on contemporary social and cultural theory.Among the traditions of thought discussed are symbolic interactionism, modern sociology, post-structuralist thought, feminist and queer theory, psychoanalysis, and postmodernism.Elliott reviews core concepts of the self through an analysis of several connected themes: the complex relation between self and society, the importance of the interpreting self in social life, the reshaping of processes of self-formation and the changing character of identity politics. The new edition continues to break new ground by introducing compelling, contemporary material on the globalization of the self. "Concepts of the Self" is an accessible and invaluable introductory text for students in the areas of social and political theory, sociology, social psychology, cultural studies and gender studies.
Keywords: Self